2019
DOI: 10.1097/jsm.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Spondylolysis in Symptomatic Adolescent Athletes: An Assessment of Sport Risk in Nonelite Athletes

Abstract: The sports with the greatest risk of spondylolysis in adolescent athletes in this study were not consistent with published literature. Clinicians should be cautious generalizing high-risk sports to their practice, as geographic region and level of the athlete may significantly influence the incidence of spondylolysis in the population they are treating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 38 publications
0
50
1
3
Order By: Relevance
“…All positive diagnoses of spondylolysis had a history of athletic participation. A similar study also found spondylolysis rates as high as 30% among 1025 adolescent athletes presenting to a sports medicine clinic for low back pain [6]. us, there is a significantly higher incidence and prevalence of spondylolysis among young athletes than those in the general pediatric population.…”
Section: Epidemiology and Natural Historymentioning
confidence: 64%
“…All positive diagnoses of spondylolysis had a history of athletic participation. A similar study also found spondylolysis rates as high as 30% among 1025 adolescent athletes presenting to a sports medicine clinic for low back pain [6]. us, there is a significantly higher incidence and prevalence of spondylolysis among young athletes than those in the general pediatric population.…”
Section: Epidemiology and Natural Historymentioning
confidence: 64%
“…Современные исследователи, изучая спондилолиз, традиционно придерживаются двух основных теорий его происхождения и развития: врожденной [9,16,17] и приобретенной [18][19][20][21][22]. Основоположником теории о врожденном происхождении принято считать Ф.л.…”
Section: материал и методыunclassified
“…Интересную информациюоб этом приводят M. Selhorst с соавторами, проанализировавшие наличие спондилолиза у людей, профессионально занимающихся различными видами спорта. Оказалось, что из 11 видов спорта у мужчин и из 14 видов спорта у женщин наиболее опасными в плане формирования спондилолиза являются бейсбол и гимнастика соответственно [22].…”
Section: материал и методыunclassified
See 1 more Smart Citation
“…Spondylolysis occurs in individuals playing sports activities, and each sport requires speci c movements and practice menu. It was reported that baseball and soccer were the greatest risk of spondylolysis in young male athletes [10]. Soccer demands several kinds of kicking, short sprints, collisions with other players and occasionally throwing a ball with the hands.…”
Section: Introductionmentioning
confidence: 99%